Exploring EFL Students’ Reading Engagement in KWL Strategy - Anisyafa Firda Dwi Damaranti; Hilmansyah Saefullah; Iwan Ridwan (INTERACTION: Jurnal Pendidikan Bahasa, 2021)
This research attempted to explore how the KWL strategy facilitates EFL students' reading engagement. The participants of this research were three students of an Islamic Senior High School. Using a case study design, the researcher describes EFL students' reading engagement by observing and engaging them in in-depth interviews. For gaining the data, the researchers used semi-structured interviews and the students' artefacts of the KWL tables. The interview session was conducted through WhatsApp audio-recording as a preferred interview media by the participants. The result of the research found that the KWL strategy gives positive engagement and self-assessment to EFL students with several stages. Other researchers are suggested to conduct further research on similar topics related to reading engagement in EFL students. Several research possibilities will expand this research. First, future researchers can complete this study by looking at the students' needs in the classroom. The results of this study revealed that students have difficulty with vocabulary.